A Phase I Randomized Study of a Specifically Engineered, pH‐Sensitive PCSK9 Inhibitor RN317 (PF‐05335810) in Hypercholesterolemic Subjects on Statin Therapy. Issue 1 (17th November 2016) - Levisetti, M; Joh, T; Wan, H; Liang, H; Forgues, P; Gumbiner, B; Garzone, PD
Abstract : This phase I study assessed the safety, tolerability, pharmacokinetics, and pharmacodynamics of RN317 (PF‐05335810), a specifically engineered, pH‐sensitive, humanized proprotein convertase subtilisin kexin type 9 (PCSK9) monoclonal antibody, in hypercholesterolemic subjects (low‐density lipoprotein cholesterol (LDL‐C) ≥ 80 mg/dl) 18–70 years old receiving statin therapy. Subjects were randomized to: single‐dose placebo, RN317 (subcutaneous (s.c.) 0.3, 1, 3, 6, or intravenous (i.v.) 1, 3, 6 mg/kg), or bococizumab (s.c. 1, 3, or i.v. 1 mg/kg); or multiple‐dose RN317 (s.c. 300 mg every 28 days; three doses). Of 133 subjects randomized, 127 completed the study. RN317 demonstrated a longer half‐life, greater exposure, and increased bioavailability vs. bococizumab. RN317 was well tolerated, with no subjects discontinuing because of treatment‐related adverse events. RN317 lowered LDL‐C by up to 52.5% (day 15) following a single s.c. dose of 3.0 mg/kg vs. a maximum of 70% with single‐dose bococizumab s.c. 3.0 mg/kg. Multiple dosing of RN317 produced LDL‐C reductions of ∼50%, sustained over an 85‐day dosing interval.